87 Effects of Community Falls Prevention Service Closure on ICD-10 Coded Fracture Rates in Older People: An Interrupted Time Series Approach. (6th February 2020) - McCarthy, A; McMeekin, P; Anderson, G; McCarthy, S; Parry, S W
Abstract: Introduction: Guidelines on falls prevention recommend case ascertainment based on opportunistic case ascertainment and referral in those who have fallen. In October 2009 we implemented a novel multidisciplinary, multifactorial falls, syncope and dizziness service with enhanced case-ascertainment through proactive, primary care-based screening for associated risk factors. In addition to comprehensive geriatric assessment, 25% of 4032 service participants underwent strength and balance training. The baseline outcomes have been previously reported.1 Funding was withdrawn, and the service closed on 31/01/2014. We examined the effect of service-closure on fractures presenting to secondary care with and without the service running. Methods: An interrupted time series method was used. ICD-10 coded fracture numbers attending secondary care were determined (Hospital Episode Statistics from 01/02/2012-31/05/2017) for all North Tyneside residents ≥60 years at the time of service closure, including 25-months with, and 40-months without, service provision. Results: There was a 0.9% (p=0.018) monthly reduction in falls over 25-months of service provision which increased during the winter months of a 9.8% (p=0.015) increase. In the month following the service closure there was an initial increase in fractures of 8.5% (p=0.231), followed by an increase in the monthly time trend of 1% (p=0.018). This resulted in a post-service monthly increase in fractures of 0.1%, an estimated extra 625 fractures over the 40-month post-service cessation period. At an average £8600 per fracture, the estimated cost may have been £5, 375, 000. Conclusions: In this naturalistic experiment, following an initial drop in fractures, disinvestment in this service resulted in a rise in elders' fractures presenting to secondary care. The closure of the service may have had a large unintended cost, averaging £1.5 million annually, versus annual running costs of £220, 000. Further research is needed to control for patient-level characteristics and to establish the cost-effectiveness of the service.